Spiritual relaxation to reduce dysmenorrhea: a quasy experimental - A'yun, Qurota; Mukhoirotin, Mukhoirotin (Universitas Muhammadiyah Purwokerto, 2019)
Background: The dysmenorrhea prevalence is still reported high in the world. Several previous studies discovered that deep breathing relaxation effectively reduced dysmenorrhea. Other studies presented the combination of early mobilization and spiritual relaxation could reduce the level of client pain postoperative appendectomy, however the effectiveness of spiritual relaxation techniques to reduce dysmenorrhea is not yet tested.Objective: to determine the effect of spiritual relaxation to reduce dysmenorrhea.Method: The research design used was Quasi Experiment with the pretest-posttest Control Group Design approach. The populations were female students who experienced menstrual pain (dysmenorrhea) and met the inclusion and exclusion criteria. The variable in this study was dysmenorrhea. The sampling technique was simple ramdom sampling consisted of 44 respondents. The calculation instrument was NRS (Numeric Rating Scale) and data were analyzed through statistical test of Paired T-Test and Independent T-Test.Results: After spiritual relaxation treatment, the intensity of menstrual pain reduced significantly from 6.05 - 1.77, it proved that there was an effect of spiritual relaxation on dysmenorrhea with a significant value (ρ) of 0.000 (p ≤ 0.05). There were significant differences in the intensity of menstrual pain in the intervention and control groups (1.77 ± 1,109 vs 5.63 ± 0.445; p> 0.05).Conclusion: Spiritual relaxation effectively reduces dysmenorrhea